NILAI BUDAYA PADA INTERIOR MUSEUM SONOBUDOYO YOGYAKARTA - Wardani, Laksmi Kusuma (Dimensi Interior, 2007)
The interior of Sonobudoyo Museum has been utilized for aesthetics, education, and tourism importance and conservation of cultural value. This museum is the result of ideas integrating the rational thinking of Deutsch architect, Thomas H. Karsten with the Java cultural value. The monumental art value and technical innovation in this building, is a process towards modernization, which has been contributing specific characteristics to the city of Yogyakarta as a cultural city. The erection of the building is not just referring to the functional, aesthetical,and technical concept, but also containing material and immaterial value of the Javanese society, so that the building and its environment becomes an object or material that is integrated in the museum collection. Abstract in Bahasa Indonesia : Interior Museum Sonobudoya dimanfaatkan untuk kepentingan estetik, pendidikan, pariwisata dan pelestarian nilai budaya. Museum ini merupakan wujud gagasan yang mengabungkan pemikiran rasional arsitek Belanda Thomas H. Karsten dengan nilai-nilai budaya Jawa. Nilai monumental seni dan inovasi teknik pada bangunan ini, merupakan proses menuju pembaharuan, yang memberi karakter khusus Yogyakarta sebagai kota budaya. Pendirian museum ini bukanlah sekadar mengacu pada konsep fungsi, estetika dan teknik saja, melainkan memuat nilai material dan imaterial masyarakat Jawa, sehingga bangunan dan lingkungannya menjadi obyek atau materi yang menyatu dengan koleksi museum. Kata kunci: Makna, Interior, Museum Sonobudoyo